Experimental study on the cyclic behavior of loose calcareous sand under linear stress paths - Zhou, Xiao-zhi; Chen, Yu-min; Liu, Han-long; Zhang, Xin-lei (Marine georesources & geotechnology, 2020)
Hollow cylinder torsional shear tests on loose isotropically and anisotropically consolidated calcareous sand were conducted to investigate the cyclic behavior under three different linear stress paths, including horizontal line, oblique line, and vertical line stress paths, in a coordinate system of the normal stress difference and the horizontal shear stress. The dominant strain components of the isotropically consolidated specimens are affected by the stress paths. With increasing consolidation stress ratio, axial strain gradually becomes the dominant strain component under the three different stress paths. The cyclic strength of the isotropically consolidated specimens under the three different stress paths are almost the same, while for the anisotropically consolidated specimens, the cyclic strengths are strongly affected by the stress paths. These results indicate that conventional cyclic triaxial tests may overestimate cyclic strength in some cases. Irrespective of the stress paths and cyclic stress ratios, the terminal residual excess pore pressure ratio decreases with increasing consolidation stress ratio. Moreover, an empirical equation is proposed to describe the relationship between the normalized shear work and the normalized residual excess pore pressure ratio. The comparative study reveals that the relationship proposed for silica sand is not suitable for the dynamic analyses of calcareous sand.